Pulsar scattering and the ionized interstellar medium - Geyer, M (2017)
Fifty years after the discovery of the first pulsating neutron star, the field of pulsar science has grown into a multidisciplinary research field, working to address a wide range of problems in astrophysics -- from stellar evolution models to high precision tests of General Relativity to analysing the detailed structure of the Interstellar Medium in the Milky Way. Over 2500 Galactic pulsars have been discovered. The next generation telescopes, such as the Square Kilometre Array, promise to discover the complete observable Milky Way population, of several tens of thousands, over the next decade. These point sources in the sky have extreme properties, with matter densities comparable to that of an atomic nucleus, and surface magnetic fields a trillion times stronger than Earth's magnetic field. Observationally, the most valuable property is their rotational stability -- allowing us to anticipate and sum their beamed radio emission, as the pulsar spins around its axis, on millisecond to second timescales. The detected radio wave signals carry with them information of the ionised interstellar medium (IISM) paths they traveled along. The imprints reveal that the pulsar signals we detect travel along multiple paths. While the bulk of the emitted signal propagates along a straight line, we also receive delayed emission scattered through small angles, back into our line of sight. This scattering is caused by fluctuations in the free electron densities of the IISM. The impact of these inhomogeneities is exaggerated at low observing frequencies, where averaged pulsar profiles are observed to be broadened, and showcase exponential scattering tails characterised by a scattering timescale г. Simple theoretical models predict a power law dependence of г on frequency, with a spectral index α = 4. Despite these predictions, my analysis of pulsar data in this thesis, reveal a more complex frequency dependence on г. I investigate the scattering characteristics of a set of pulsars observed by the Low Frequency Array (LOFAR), at 110~MHz to 190~MHz. These data are ideal datasets for accurate studies of pulsar scattering, providing broad frequency bands at low frequencies. I find anomalously low power law spectral indices, α, describing the frequency dependence of г. These indices are likely due to anisotropic scattering mechanisms or small scattering clouds in the IISM. To conduct effective data analysis, I develop scattering fitting techniques by first analysing IISM effects on simulated pulsar data. I investigate the effects of two different types of scattering mechanisms, isotropic and anisotropic scattering, and consider each of their particular frequency-dependent impacts on pulsar data. The work on simulated data provides a robust fitting technique for extracting scattering parameters and a framework for the interpretation of the LOFAR data used in this study. The fitting technique simultaneously models scattering effects and standard frequency-dependent pulse profile evolution. I present results for 13 pulsars with simple pulse shapes, and find that г, associated with scattering by a single thin screen, has a power law dependence on frequency with α ranging from 1.50 to 4.0. My results show that extremely anisotropic scattering can cause low α measurements. The anomalous scattering properties can also be caused by the presence of small scattering clumps in the IISM, as opposed to the conventionally modelled large scattering screens. Evidence for both anisotropic scattering and small scattering clouds with high electron densities come from other areas of research. Indications of the anisotropic nature of the local IISM mostly come from high resolution pulsar scintillation analyses, while evidence for high density scattering clouds is often based on extreme scattering events measured through quasar observations. My results suggest that these anomalous scattering properties are more prevalent than formerly thought, prompting us to reconsider the physical conditions of the IISM, where traditionally high electron densities are reserved for HII regions and anisotropy is not modelled. High quality, low frequency pulsar data, where anomalous propagation effects become measurable, are a valuable addition in assisting us to distinguish between the different physical mechanisms that can be at play. The more complex these IISM characteristics reveal themselves to be, the harder it will be to disentangle intrinsic profile emission from IISM propagation imprints. Successfully separating these effects, however, promises to improve our understanding of the intrinsic pulsar radio emission -- a process that is still poorly understood.